A contística das águas como escrita do desastre e da catástrofe: vidas viradas pelo avesso na Pan-Amazônia - SOUZA, Irisvaldo Laurindo de (Universidade Federal do Pará, 2023)
This master's thesis is the result of a research that investigated the representation of waters in the Amazonian literature, focusing on contouring that has as its leitmotiv the typical hydrological disasters of the region. Among them the Andean "llocllada", the fallen lands, the floods and the fluviomarine tide known as pororoca. The corpus consists of six short stories by four authors: "Terra caída", by Alberto Rangel (2008), part of the book Inferno Verde; "La llocllada" and "Sob as primeiras estrelas" [Cielo sin nubes], by the Peruvian writer Francisco Izquierdo Ríos (1975; 2010); "A flood", by the Amazonian writer Arthur Engrácio (1995); and "Poraquê" and “Mamí tinha razão", by the Paulista writer living in Pará João Meirelles Filho (2017). This research adopts the comparative method and its approach is qualitative, based on bibliography. The main hypothesis was to observe how water disruption impacts the Amazonian subject's experience both on his direct relationship with nature and on his relations with the prevailing social order. The theoretical axis that guides the investigation is the concept of catastrophe, taken from contemporary philosophical thought but directly articulated with the Aristotelian doctrine of human power. The second theoretical key used is the concept of disaster, brought from sociological thought and also epistemologically linked to the power of the natural act in Aristotle's doctrine. With this instrumental, the analytical reading of water contouring is undertaken as an allegorization of the Amazonian man's modus vivendi and of his problematic and sometimes traumatic exposure to the powers that govern the actions of Nature and the facts of Culture. The critical interpretation of literary texts by authors from different periods and aesthetic affiliations thus provides a reflection on the fractures that water disasters cause in daily life and in the experience of individual and collective subjects in the Pan-Amazon, as well as on the traumas imposed on them in late Modernity as a result of the advance of the capital's civilization on the Amazonian border.